2018
DOI: 10.15294/jdm.v9i1.14649
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Competitive Advantage of SMEs in East Java, Indonesia

Abstract: This article describes the situation and potential of SMEs in East Java Indonesia. Small and medium enterprises are essential to support the economic progress of a country. By using descriptive analysis and multiple regression then generated mapping. Mapping the characteristics and competitiveness of SMEs is done as a basis for gap analysis. If the current condition of Indonesian SMEs is known, benchmarking can be done by comparing ideal conditions or targets to be achieved in the face of global competition. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 15 publications
0
9
0
6
Order By: Relevance
“…This is quite reasonable considering that the SMEs sector has the prospect of being developed, also has different characteristics with large companies (HC et al, 2019). However, this SME can still be seen as a weak business performance (Tobing et al, 2018). It found that about 27% of SMEs have competitiveness, while 73% have no competitiveness (Lewuk & Japi, 2017).…”
Section: Introductionmentioning
confidence: 90%
“…This is quite reasonable considering that the SMEs sector has the prospect of being developed, also has different characteristics with large companies (HC et al, 2019). However, this SME can still be seen as a weak business performance (Tobing et al, 2018). It found that about 27% of SMEs have competitiveness, while 73% have no competitiveness (Lewuk & Japi, 2017).…”
Section: Introductionmentioning
confidence: 90%
“…Interaksi jaringan memberikan peluang untuk pembelajaran, karena para pelaku UMKM dalam kegiatan operasionalnya menciptakan tanggapan terhadap perubahan di dalam lingkungannya. Keunggulan yang dimiliki oleh UMKM memiliki hambatan komunikasi yang lebih sedikit dibandingkan dengan fungsi berbagi pengetahuan tentang kegiatan tersebut untuk membantu operasi perubahan ke arah strategis bagi perkembangan organisasi yang lebih besar (Tobing, Fathorazzi, & Wulandari, 2018).…”
Section: Faktor Internal Dan Eksternalunclassified
“…Studi Tobing, Fathorazz & Wulandari (2018) menemukan bahwa kemampuan inovasi merupakan faktor yang secara signifikan mempengaruhi keunggulan kompetitif UKM di Jawa Timur. Menggunakan metode analisis regresi berganda, hasil studi menyimpulkan semakin tinggi kemampuan inovasi, fokus pada strategi bisnis, dan respon terhadap perubahan yang terjadi, semakin memperkuat keunggulan kompetitif UKM (Tobing et al, 2018). Pengujian peran mediasi keunggulan kompetitif dalam studi ini dilakukan secara lebih komprehensif, yaitu melalui metode analisis Partial Least Square Structural Equation Model (PLS-SEM).…”
Section: Tinjauan Literatur Dan Hipotesisunclassified
“…Selain itu sejalan dengan pernyataan Yacob et al (2017), bahwa perusahaan yang mampu menciptakan keunggulan kompetitif akan memiliki kekuatan untuk bersaing dengan perusahaan lain karena produknya tetap diminati oleh pelanggan. Hasil studi ini memiliki kesamaan dan memperkuat penelitian sebelumnya Budiastuti & Versia (2011) , Zhou et al (2009, dan Tobing et al (2018) bahwa keunggulan bersaing memiliki pengaruh yang signifikan terhadap kinerja bisnis. Hasil studi menguatkan temuan penelitian Ismail et al (2017) bahwa kinerja ekspor dimediasi keunggulan kompetitif.…”
Section: Diskusiunclassified